Preface of the special issue quantum foundations: information approach - D'Ariano, Giacomo Mauro (Philos Trans A Math Phys Eng Sci, 2016)
This special issue is based on the contributions of a group of top experts in quantum foundations and quantum information and probability. It enlightens a number of interpretational, mathematical and experimental problems of quantum theory.